The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.18632/oncotarget.22637
|View full text |Cite
|
Sign up to set email alerts
|

Acid ceramidase and its inhibitors: a de novo drug target and a new class of drugs for killing glioblastoma cancer stem cells with high efficiency

Abstract: Glioblastoma remains the most common, malignant primary cancer of the central nervous system with a low life expectancy and an overall survival of less than 1.5 years. The treatment options are limited and there is no cure. Moreover, almost all patients develop recurrent tumors, which typically are more aggressive. Therapeutically resistant glioblastoma or glioblastoma stem-like cells (GSCs) are hypothesized to cause this inevitable recurrence. Identifying prognostic biomarkers of glioblastoma will potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 50 publications
2
64
0
1
Order By: Relevance
“…Doan et al identified Carmofur as an ASAH1 inhibitor that can cross the blood-brain barrier. It is highly effective and targets glioblastoma cancer stem cells [116]. Carmofur is an approved drug against colorectal cancer in Japan [117].…”
Section: Ceramidase Inhibitorsmentioning
confidence: 99%
“…Doan et al identified Carmofur as an ASAH1 inhibitor that can cross the blood-brain barrier. It is highly effective and targets glioblastoma cancer stem cells [116]. Carmofur is an approved drug against colorectal cancer in Japan [117].…”
Section: Ceramidase Inhibitorsmentioning
confidence: 99%
“…In support, it was reported that administration of the functional S1P antagonist FTY720 to nude mice led to downregulation of S1P receptors, induced apoptosis in GSCs, and was synergistic with TMZ in promoting cytotoxicity [232]. Of relevance, the apoptosis induced by inhibiting SphKs was shown to be highly effective, and to specifically target GSCs [220], known as resistant cells to the standard GBM chemotherapy agent TMZ.…”
Section: S1p In the Cancer Microenvironment Promotes Death Resistancementioning
confidence: 94%
“…In particular, it was found that SphK1 inhibition: (1) leads to cell death by inducing apoptosis of human GBM cells and xenografts, and reduces survival in orthotopic GBM [72,177]; (2) sensitizes GBM cells, and different cancer cells, to several cytotoxic drugs [216]; (3) is effective in potentiating the cytotoxicity of both TMZ and radiation therapy in various human GBM cell lines [217,218]; and (4) induces apoptosis and inhibits colony formation in TMZ-resistant GBM cells [219]. Of relevance, recent studies on GBM irradiated cells revealed that S1P is upregulated, and SphK1 gene significantly induced following radiation, suggesting that S1P links to radio-resistance and increased aggressiveness of irradiated GBM cells [69,220].…”
Section: S1p In the Cancer Microenvironment Promotes Death Resistancementioning
confidence: 99%
“…Subsequent inhibition of acid ceramidase using N-oleoylethanolamine, was found to suppress this increase in ASAH1 expression, resulting in increased ceramide accumulation [149]. Elevated ASAH1 levels have been reported in the tumors of patients with newly diagnosed GBM, as well as radiotherapy-treated GBM, correlating with poor survival [165,166]. This elevation of ASAH1 in response to radiation has also been reported in both adult (U87) and pediatric (SJGBM-2) GBM cell lines, as well as patient tissue samples [165,166].…”
Section: Acid Ceramidasementioning
confidence: 99%
“…Elevated ASAH1 levels have been reported in the tumors of patients with newly diagnosed GBM, as well as radiotherapy-treated GBM, correlating with poor survival [165,166]. This elevation of ASAH1 in response to radiation has also been reported in both adult (U87) and pediatric (SJGBM-2) GBM cell lines, as well as patient tissue samples [165,166]. The mechanism by which this resistance occurs is thought to be through a reduction in ceramide accumulation, and an upregulation of S1P, resulting in increased cell viability [166].…”
Section: Acid Ceramidasementioning
confidence: 99%